2019
DOI: 10.1021/acs.jcim.9b00513
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Unbinding Pathways of Products Formed in Catalytic Reactions Involved in SIRT1–3: A Random Acceleration Molecular Dynamics Simulation Study

Abstract: Sirtuins are a family of nicotinamide adenine dinucleotide (NAD + )-dependent enzymes, which undergo robust deacetylase activity, resulting in the production of nicotinamide. It is well known that nicotinamide, which is one of the products, can also act as an inhibitor for further deacetylation process by forming NAD + again. Hence, the removal of nicotinamide from sirtuins is a demanding process, and the mechanistic understanding of the process remains elusive. In this investigation, we have made an attempt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
(80 reference statements)
1
9
0
Order By: Relevance
“…Visual inspections of trajectories revealed different states of the cofactor-binding loop even for the same system across replicas, which showed the flexible nature of this loop and limited sampling of its conformational degrees of freedom during 200 ns of unbiased MD (Figure A). Results of RMSF analysis were in agreement with previously reported MD studies of SIRT2. Considering the fact that the cofactor-binding loop’s PHE-96 and ARG-97 constitute the entrance of the inhibitor binding pocket (substrate-binding site, Figures and ), single static X-ray structures should be taken with caveats in the structure-based design campaigns. Additionally, visual inspection of trajectories revealed that some of the ligands exhibited multiple binding modes within the binding site during the MD simulations.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Visual inspections of trajectories revealed different states of the cofactor-binding loop even for the same system across replicas, which showed the flexible nature of this loop and limited sampling of its conformational degrees of freedom during 200 ns of unbiased MD (Figure A). Results of RMSF analysis were in agreement with previously reported MD studies of SIRT2. Considering the fact that the cofactor-binding loop’s PHE-96 and ARG-97 constitute the entrance of the inhibitor binding pocket (substrate-binding site, Figures and ), single static X-ray structures should be taken with caveats in the structure-based design campaigns. Additionally, visual inspection of trajectories revealed that some of the ligands exhibited multiple binding modes within the binding site during the MD simulations.…”
Section: Resultssupporting
confidence: 86%
“…This intricate structural heterogeneity of SIRT2 indicates the importance of additional dynamical considerations in the discovery of SIRT2 inhibitors and points out the complexity of rationalization of structure–activity relationships. Although several computational studies examined the dynamical behavior of SIRT2, none of them provided a detailed characterization of pocket dynamics. Under the assumption that the available X-ray structures do not describe all of the “druggable” conformational states of the binding pocket, a description of the full SIRT2 pocket dynamics could be beneficial in the design of more selective, more potent, and novel chemical species of inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The random acceleration molecular dynamics (RAMD) studies were carried out to further substantiate the conformational changes in loop-2 nucleotides, during unbinding pathways of TGP18 from BCL-2 structure (Figure 2 C) 53 . Five different configurations (state I-V) for Mode I binding along the egression (unbinding) pathway were collected and change in nucleotide residue wise contributions to binding free energy were estimated using MM-GBSA calculations and decomposition analysis ( Figure S17 and Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been reported for the human isotype Sirt2 in the modulation of cancer pathogenesis, inflammation, metabolic diseases, and neurodegeneration, projected the regulation of Sirt2 activity as a promising approach for pharmaceutical intrusions 66 . In this context, functions of Sirt2 in the cellular environment to some extend have been elucidated and several crystal structures in complex with selective and/or potent inhibitors were also resolved [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%